(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
In this research, the trapezoidal shaped chevron plate heat exchanger (PHE) is simulated using computational fluid dynamics (CFD) software to determine its heat transfer capacity and friction factor. The PHE is modelled with chevron angles from 30° to 60°, and also the performances are compared with the plain PHE. The validation is done by comparing simulation result with published references using 30° trapezoidal chevron PHE. The Nusselt number and friction factor obtained from simulation model is plotted against different chevron angles. The Nusselt number and friction factor is also compared with available references, which some of the references used sinusoidal chevron PHE. The general pattern of Nusselt number and friction factor with increasing chevron angle agrees with the references. The heat transfer capacity found in current study is higher than the references used, and at the same time, the friction factor also increased. Besides this, it is also found that the counter flow configuration has better heat transfer capacity performance than the parallel flow configuration.